Scots hit out at WHS. - Fraser, Fiona (Bookseller, 2004)
Scottish parliamentarian Kenny MacAskill and the Scottish Publishers Association have launched a scathing attack on books retailer WH Smith for failing to stock sufficient Scottish interest titles. It follows the news that the chain has put additional restrictions on buying titles from local interest publishers across Great Britain. MacAskill criticised the retailer for having no purchasing policy to buy Scottish books. Timothy Wright, m.d. of publisher Edinburgh University Press and chairman of the Scottish Publishers Association, claimed that the chain's central systems did not recognise Scottish titles for national distribution.